Comparitive study between button-hole tympanoplasty and tympanoplasty with placement of graft lateral to handle of malleus with or without cortical mastoidectomy in mucosal type of chronic otitis media - Ahmed, J. Mansoor; ., Panchami (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Various techniques of underlay graft placement have been described in literature. In this study we compare two simple underlay techniques of temporalis fascia graft placement that is Buttonhole tympanoplasty and tympanoplasty with placement of graft lateral to handle of malleus in mucosal type of chronic otitis media patients undergoing tympanoplasty to find out which among the two is a better technique based on the audiological improvement post-operatively. Methods: This is a case series study which included 30 patients undergoing type-1 tympanoplasty. Group A with 15 patients underwent Buttonhole tympanoplasty and Group B with 15 patients underwent tympanoplasty with placement of graft lateral to handle of malleus. Results: Post-operative hearing improvement was assessed after duration of three months. In Group A, 13 (87%) patients showed hearing within normal limits and 2 (13%) patients showed mild conductive hearing loss. In Group B, 9 (60%) patients showed hearing within normal limits and 6 (40%) of patients showed mild conductive hearing loss. Both the techniques were statistically significant. Conclusions: Both the techniques mentioned are simple and effective procedures. Buttonhole tympanoplasty was considered as superior technique among the two as the handle of malleus provides better anchoring for the temporalis fascia graft, intra-operative manoeuvring of the graft is easier without causing displacement of the graft, there is no reduction in the middle ear space and post-operative hearing improvement is excellent. When the handle of malleus is eroded surgeon can perform tympanoplasty with placement of graft lateral to handle of malleus.